Professionalism, Workload, and Organizational Climate: Their Impact on Employee Productivity - Manafe, Elbert; Riwu Kore, Jefirstson R; Wadud, Muhammad; Marnisah, Luis (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: The study aims to analyze and prove the influence of professionalism, workload, and organizational climate on employee productivity. Methodology: The research design used is quantitative research. The population of the study was all employees of the Kupang City DPRD Secretariat, totaling 97 employees. All employees became research samples with saturated sampling techniques. The data was obtained through questionnaire interviews (Likert scale), observation, and documentation. The research data consists of primary and secondary data. The data analysis method is multiple linear regression analysis. Results: The results of the study showed a t-value of professionalism of 2.712 > t-table of 1.9852. Workload has a t-value of 3.459 > t-table of 1.9852. The t-value of organizational climate is 11.442 > t-table of 1.9852, and the F-value of 365.582 > F-table of 2.70, which indicates that professionalism, workload, and organizational climate have a positive and significant effect on employee productivity at the Kupang City DPRD Secretariat both partially and simultaneously. The three exogenous variables have a "strong" correlation to performance with an R2 value of 92.2%. Findings: This study highlights the importance of high employee professionalism, the suitability of employee workload, and maintaining a conducive organizational climate to achieve high employee productivity. Novelty: This study elaborates on the interaction between professionalism, workload, and organizational climate in the context of employee productivity in government organizations. Originality: This study contributes to the literature on employee productivity at the Kupang City DPRD Secretariat by addressing the gap in understanding these variables. Conclusion: Practical thinking is a recommendation for the DPRD Secretariat organization to develop strategies to increase employee productivity in line with the organization's expectations and goals.  The population of the study was ASN in the Secretariat of the Kupang City DPRD. It is also important that the study be conducted on Members of the Kupang City DPRD as the highest political decision makers in the institution. Type of Paper: Quantitative empirical research.